Therapy using implanted organic bioelectronics - Amanda Jonsson; Zhiyang Song; David Nilsson; Björn A. Meyerson; Daniel T. Simon; Bengt Linderoth; Magnus Berggren (2015)
Many drugs provide their therapeutic action only at specific sites in the body, but are administered in ways that cause the drug's spread throughout the organism. This can lead to serious side effects. Local delivery from an implanted device may avoid these issues, especially if the delivery rate can be tuned according to the need of the patient. We turned to electronically and ionically conducting polymers to design a device that could be implanted and used for local electrically controlled delivery of therapeutics. The conducting polymers in our device allow electronic pulses to be transduced into biological signals, in the form of ionic and molecular fluxes, which provide a way of interfacing biology with electronics. Devices based on conducting polymers and polyelectrolytes have been demonstrated in controlled substance delivery to neural tissue, biosensing, and neural recording and stimulation. While providing proof of principle of bioelectronic integration, such demonstrations have been performed in vitro or in anesthetized animals. Here, we demonstrate the efficacy of an implantable organic electronic delivery device for the treatment of neuropathic pain in an animal model. Devices were implanted onto the spinal cord of rats, and 2 days after implantation, local delivery of the inhibitory neurotransmitter γ-aminobutyric acid (GABA) was initiated. Highly localized delivery resulted in a significant decrease in pain response with low dosage and no observable side effects. This demonstration of organic bioelectronics-based therapy in awake animals illustrates a viable alternative to existing pain treatments, paving the way for future implantable bioelectronic therapeutics.